Shotgun MS proteomic analysis of bronchoalveolar lavage fluid in normal subjects. Issue 10 (October 2014) - Nguyen, Elizabeth V.; Gharib, Sina A.; Schnapp, Lynn M.; Goodlett, David R.
Abstract : We provide a review of proteomic techniques used to characterize the bronchoalveolar lavage fluid (BALF) proteome of normal healthy subjects. Bronchoalveolar lavage (BAL) is the most common technique for sampling the components of the alveolar space. The proteomic techniques used to study normal BALF include protein separation by 2DE, whereby proteins were identified by comparison to a reference gel as well as high pressure liquid chromatography (HPLC)‐MS/MS, also known as shotgun proteomics. We summarize recent progress using shotgun MS technologies to define the normal BALF proteome. Surprisingly, we find that despite advances in shotgun proteomic technologies over the course of the last 10 years, which have resulted in greater numbers of proteins being identified, the functional landscape of normal BALF proteome was similarly described by all methods examined.